2015
DOI: 10.1002/ejoc.201403475
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Promoted Reactivity of Alkenes in Dehydrogenative Heck Reactions of Furans and Thiophenes

Abstract: 4,5‐Diazafluorenone was found to promote the dehydrogenative Heck reaction of furans and thiophenes with hindered alkenes. High stereoselectivity was achieved in the synthesis of β,β‐diaryl α,β‐unsaturated alkenes. A mechanism, based on ESI‐MS studies, kinetic experiments, and competitive reactions, was proposed. The ligand influences C–H bond activation, insertion of the alkenes, the stereodetermining step, and the aerobic regeneration of the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…DAF/Pd(OAc) 2 proved to be an effective catalyst for aerobic allylic C–H acetoxylation of allyl benzene and numerous other terminal alkene substrates. Subsequent studies have shown that DAF is uniquely effective in a number of other Pd-catalyzed aerobic oxidation reactions, including oxidative C–C and C–O coupling reactions with arenes, 18 α,β-dehydrogenation of cyclic ketones, 19 oxidative Heck reactions, 20 and also various non-aerobic oxidation reactions. 21 …”
Section: Introductionmentioning
confidence: 99%
“…DAF/Pd(OAc) 2 proved to be an effective catalyst for aerobic allylic C–H acetoxylation of allyl benzene and numerous other terminal alkene substrates. Subsequent studies have shown that DAF is uniquely effective in a number of other Pd-catalyzed aerobic oxidation reactions, including oxidative C–C and C–O coupling reactions with arenes, 18 α,β-dehydrogenation of cyclic ketones, 19 oxidative Heck reactions, 20 and also various non-aerobic oxidation reactions. 21 …”
Section: Introductionmentioning
confidence: 99%
“…[2] Prominent examples include the Wacker process, [3] alcohol oxidation, [4] Wacker-type cyclization [5] and the Fujiwara-Moritani (dehydrogenative/oxidative Heck) reaction. [ 6] The majority of Pd-catalyzed aerobic oxidations proceed through a catalytic cycle wherein Pd II mediates substrate oxidation and Pd 0 is reoxidized by O 2 (Scheme 1). [7] The Pd 0 intermediate in this cycle is metastable and susceptible to decomposition via aggregation into Pd nanoparticles and/or bulk metallic Pd.…”
mentioning
confidence: 99%
“…First, L should sufficiently provide electron density towards the metal but still maintain moderate steric hindrance . Second, it should not promote intramolecular deprotonation of the Pd−H bond, which thus rules out a good number of bidentate nitrogen ligands . Third, it should operate under neutral conditions to preserve the chemical integrity of both the Pd−H species and the substrate.…”
Section: Methodsmentioning
confidence: 99%